The Effect of Compensation and Work Environment on Production Employee Performance with OCB As Mediation Variable : Case Study of CV. Berlian Makmur in Situbondo - Nadia Mega Oktavia; Uci Yuliati; Dicky Wisnu Usdek Riyanto (Universitas Muhammadiyah Malang, 2022)
The purpose of the study was to determine the effect of compensation and work environment on employee performance with organizational citizenship behavior as mediation at CV Berlian Makmur in Situbondo Regency. The population in the study was 55 production employees. The sampling technique is total sampling. Data collection through questionnaires and interviews. The analysis method uses a range of scales and linear regression analysis techniques with SmartPLS 2.0. The results showed that compensation and work environment had a positive and significant effect on employee performance partially. Compensation has no significant effect on organizational citizenship behavior. The work environment has a positive and significant effect on organizational citizenship behavior. Organizational citizenship behavior has a positive and significant effect on employee performance. Organizational citizenship behavior does not mediate compensation for employee performance. Organizational citizenship behavior mediates the work environment on employee performance.